Comparison of Two Perennial Grass Breeding Systems with Switchgrass. Issue 3 (1st May 2013) - Vogel, K. P.
ABSTRACT: Two breeding systems, between‐ and within‐family selection (BWFS) and multistep family selection (MFS), were compared using three switchgrass ( Panicum virgatum L.) populations to determine which system was the most effective in improving biomass yield and in vitro dry matter digestibility (IVDMD). With BWFS, half‐sib families are produced and evaluated on a family basis and then the best plants within the best families are selected for crossing to produce a new strain. With MFS, parent genotypes of the half‐sib families being evaluated in the BWFS selection nursery are maintained and the genotypes whose progeny were the best in the BWFS evaluation trial are selected and polycrossed to produce a new strain. Methods were compared using two populations in which improved biomass yield and IVDMD were the selected traits and with a population for which improved IVDMD and winter survival were the selected traits. For the populations for which yield was a selection criteria, the BWFS breeding system produced strains with significantly greater biomass yields than the MFS system. For one of these populations, the BWFS and MFS systems did not differ for IVDMD but the MFS system produced a strain with higher IVDMD for the other population. For the population in which IVDMD and winter survival were the selection criteria, the BWFS strain had greater IVDMD than the MFS strain. Overall, the BWFS system was superior and required less work.